The relationship between burnout and postive personal resources in a sample of medicals - Ortiz Sánchez, Diana (2017)
Medicals, in the exercise of their profession, usually present a series of risk factors for the development of the Burnout, due to aspects such as, long working hours, shift shifts, little personnel and a great demand for attention; Some positive resources of the personality such as commitment, self-control, the expression of emotions, among others, have been considered fundamental to explain and address this problem. The main objective of the present study was to establish the correlation that exists between the dimensions of the syndrome and the positive personal resources evaluated. 249 physicians from a third level hospital participated, 69% (171) were men and 31% (78) women. The variable of Positive Personality called Commitment, correlated in a negative and significant way with the three dimensions of the Syndrome (exhaustion, distancing and loss of expectations). Stimulating the strengthening of the factors associated with the personality dimension commitment, will allow to maintain health in the medical staff.